P237 Hepatitis c among men who have sex with men in greater manchester – the baseline survey. (18th May 2015) - Ireland, Georgina; Ward, Chris; Ahmad, Sameena; Goorney, Ben; Higgins, Steve; Stewart, Catherine; Lattimore, Sam; Lee, Vincent
Abstract : Background/introduction: The number of HIV affected men who have sex with men (MSM) co-infected with hepatitis C (HCV) continues to rise, driven by high risk sexual practice. Aim(s)/objectives: To determine HCV burden and associated risk behaviours among MSM in Greater Manchester. Methods: Between April and October 2014, all MSM attending four GUM clinics were asked to complete a risk assessment questionnaire and HCV screening was offered. Results: There were significant differences in risk behaviour between HIV positive and HIV negative MSM (p < 0.05). Certain risk behaviours were strongly associated with HCV acquisition including: unprotected anal sex, sex with known HCV partners, fisting, group sex, 'slamming' and recreational drug use (p < 0.002). Discussion/conclusion: Our study shows HIV positive MSM have significantly different sexual behaviour which may explain the higher HCV burden. However, HCV was found in HIV negative MSM engaging in high risk sexual practices. All MSM attending sexual health clinics must have a risk assessment and HCV screening should be offered based on the risk. Further studies are warranted to look at the difference in HCV transmission according to the HIV status.